Laying the Foundation of Teaching in Digital Era: What Happens to Teachers when Technology Changes Rapidly - Suryani, Adi (Proceeding of International Conference on Teacher Training and Education, 2016)
Teachers may not always obtain professional training to improve themselves. Frequently, they have to learnby themselves, explore ways by their own, and do some trials and errors. They can be successful or fail.They have to do their own learning journey. This frequently happens when teachers have to work with ICT.The flourish, popularity and reputation of ICT in education seem very appealing, but at the same timeprovide new challenges. The Interactivity, creativity, affection, cognition, speed and transferability featuresof ICT may tempt teachers to use it in their teaching. However, teachers may face difficulty when they haveto change by adopting new technology, but they do not know what to do, where to start and who can or willhappily help them, especially when other teachers are busy with their own works. This indicates that thecoming of ICT bring joy, but also difficulty for teachers. This ICT learning difficulties/challenges areheightened by the nature of ICT which changes and expands rapidly. In this study, I intend to express myreflection on my own teaching practice and my analysis on one of my colleagues teaching experience in ourICT self-learning: what issues we encounter, what we obtain and miss in our learning journey, and whataspects affect our learning. We find that professional help for teachers does not always come when it isneeded. There are many times when teachers should face their teaching field independently (withoutprofessional training). However, we find that embedding ICT into teaching-learning now becomes not onlya trend, but also a need. To do this, teachers should be explorative, adaptive and reflective learners. Thereare many challenges that we have to face during the learning process which relate to teacher, students andenvironment aspects which require us to do exploratory, experiential and social learning. Genuine learningmay come from self-learning on what we need in our teaching practice and observation on whatenvironment provides or not provide for our learning.